FAKTOR KUNCI DALAM PENGEMBANGAN KELEMBAGAAN AGROFORESTRY PADA LAHAN MASYARAKAT - Ruhimat, Idin Saepudin (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2016)
The aims of  this study to determine the key factors in the institutional development of  agroforestr y in the community land. Research was conducted in Majenang District, Cilacap Regency, Central Java Province during April to December 2014. Data were analyzed by using Inter pretative Structural Modeling analysis. The results showed that there were three main elements in the institutional development of  agroforestr y, namely the main obstacle element, the main program and lead actors. Based on this research, it was  concluded that the key factors that must be considered in the institutional development of  agroforestr y among other, policy support, availability of  agroforestr y technology package, as well as optimization of  the involvement of  the  Cilacap Forestr y and Plantation Service Office, as well as research institutions/ university . Therefore, both central and local governments are advised to give priority to the management of  the key factors in the agroforestry institutional development.